Некоторые аспекты профессиональной подготовки будущих стоматологов методами ситуативного моделирования - Палійчук, Володимир Иванович (Actual Dentistry, 2019)
Resume. In the modern market of labor, a young dentist finds himself in unequal conditions with experienced specialists, because he has insufficient professional experience and a low level of readiness for the real conditions of practical activity. This situation requires the use in the process of professional training of future dentists in medical universities of such pedagogical technologies, methods of education that will bring the training process as close as possible to the real conditions of practical work. The study was conducted at the Department of Orthopedic Dentistry of the Ivano-Frankivsk National Medical University with the participation of students of 2–3 courses of the specialty 221 Dentistry and teachers of specialized disciplines. The methods of situational modelling (imitation and business games, «case study», situational tasks) in the professional training of future dentists are analyzed, their advantages and disadvantages are identified, the possibilities, and feasibility of their use in the teaching of orthopedic dentistry are reviewed. The results indicate that situational modelling methods are effective in the process of professional training of future dentists, since they ensure the formation of professional competence and readiness for future professional activity. The introduction of situational modelling methods in the process of professional training of future dentists requires an understanding of their specifics and features of use in the medical university. Key words: professional training, future dentists, metods of situational modelling.